An LM test based on generalized residuals for random effects in a nonlinear model - Greene, William; McKenzie, C. (Elsevier, 2015)
We obtain an LM test for the random effects probit model. In the natural parameterization of the model the necessary derivatives are identically zero under the null hypothesis. After a reparameterization, the feasible LM test is based on generalized residuals.